INTEGRATION OF STEAM-BASED MEDIA AND PROJECT-BASED LEARNING IN MATHEMATICS LEARNING - Widya Meilinda Silahuddin; Dwi Jayanti; Hamda Hamda (Prima: Jurnal Pendidikan Matematika, 2026)
Mathematics learning today demands innovations that can develop students' higher-order thinking skills, creativity, and numeracy literacy. The integration of the Science, Technology, Engineering, Arts, and Mathematics (STEAM) approach with the Project-Based Learning (PjBL) model is one alternative that is believed to be effective in providing more contextual and meaningful learning. This study aims to analyze findings related to the effectiveness of integrating STEAM-based media and PjBL in mathematics learning through a literature review. The method used is a literature review by examining fifteen relevant articles containing empirical data regarding the application of STEAM, STEAM-based digital media, and project-based learning steps at various levels of education. The analysis was carried out by identifying patterns, similarities, and differences in the findings from each article. The results of the study indicate that the integration of STEAM and PjBL media can significantly improve critical thinking skills, creativity, numeracy literacy, and student learning outcomes. In addition, this approach also contributes to strengthening student character, such as cooperation, communication, and responsibility. Overall, the synthesis of research findings confirms that STEAM-PjBL-based mathematics learning can be an effective strategy in improving the quality of learning and meeting the demands of 21st century competencies.